Additional records on the occurrence of alien fish species in the eastern Mediterranean Sea - PERISTERAKI, P.; LAZARAKIS, G.; SKARVELIS, C.; GEORGIADIS, M.; TSERPES, G. (Mediterranean Marine Science, 2006)
Recent records on the occurrence of the species Etrumeus teres, Siganus rivulatus, Stephanolepis diaspros, Sphoeroides pachygaster, Lagocephalus sceleratus, Fistularia commersonii and Siganus luridus are presented for the Aegean, Cretan and Libyan Seas and the new record of Upeneus moluccensis in the Cretan Sea is reported.